Babylon [videorecording (DVD)] - Chazelle, Damien, 1985-; Hamilton, Olivia (Actor); Pitt, Brad, 1963-; Robbie, Margot, 1990-; Calva, Diego; Smart, Jean; Adepo, Jovan; Li, Jun Li; Byrne, P. J., 1974-; Haas, Lukas, 1976-; Minghella, Max, 1985-; Scovel, Rory; et al. (Paramount, 2023)
A tale of outsized ambition and outrageous excess, Babylon traces the rise and fall of multiple characters during an era of unbridled decadence and depravity in early Hollywood.